Research projects on health risk assessment implemented by the Hanoi School of Public Health - Hung Nguyen-Viet; Tran Thi Tuyet Hanh (2013)
The authors briefly introduce three research projects on health risk assessment at the Hanoi School of Public Health which were initiated in 2013 and are currently ongoing. Two projects, “PigRISK - Reducing Disease Risks and Improving Food Safety in Smallholder Pig Value Chains in Vietnam” and “FOODRISK - Strengthening the Capacity of Risk Assessment Application for Managing Food Safety within a Food Production-Environmental-Health Interaction Context in Vietnam,” apply the Quantitative Microbial Risk Assessment approach to assess the risks associated with microbial hazards in pork, vegetables and fish. Risk assessment due to hazardous chemicals in pork will be also undertaken within the scope of the PigRISK. The third project “Dioxin Exposure Risk Assessment and the Sustainability of Public Health Interventions at Dioxin Hot Spots in Vietnam” applies Environmental Health Risk Assessment to assess the risk of dioxin exposure through human consumption of contaminated foods at Bien Hoa and Da Nang dioxin hot spots. These research projects are financially supported by CGIAR Research Program 4 (CRP4) of the International Livestock Research Institute (ILRI), the Embassy of Switzerland to Vietnam, and the Australian Government under the Australian Development Scholarship Program.